How Can China Achieve Its Non-fossil Energy Target? An Effective Allocation of China's Renewable Electricity Consumption Obligation - Zhang, Jihong; Gao, Rui; Xu, Ninghan; Xie, Chaopeng (Frontiers in Energy Research, 2020)
Promoting the consumption of renewable energy is an important way to optimize power structure, control greenhouse gas emissions and fulfill Intended Nationally Determined Contributions (INDCs) in the Paris Agreement. China's INDCs is to reduce carbon intensity by 60–65% in 2030 (compared to 2005) and promote non-fossil energy consumption proportion in primary energy consumption to 20%. On one hand, China has accomplished its 2020 carbon intensity target in 2017; on the other hand, China also faces certain difficulties achieving the target of 15% non-fossil energy consumption proportion in 2020 and 20% in 2030. Setting appropriate annual overall renewable electricity consumption (REC) and allocating it at sub-national scales can help China reach both carbon intensity and non-fossil energy consumption proportion targets. To this end, we couple the “top-down” and “zero sum gains-data envelopment analysis (ZSG-DEA)” models to form a comprehensive model for the appropriate allocation of REC. First, the “top-down” model was used to calculate the annual overall REC based on the non-fossil energy proportion target. Second, we applied the multi-principle “ZSG-DEA” model to allocate the overall REC effectively among provinces. Based on our analysis, the total REC which can be reached by Chinese government's policy of renewable electricity consumption guarantee mechanism (REC guarantee mechanism) still needs to increase by 15.36 to 20.25% compared with the overall REC calculated by our effectiveness model. In order to achieve non-fossil energy target, 26 provinces need to increase the consumption of renewable electricity compared to their initial shares required by the REC mechanism, most of which are developed coastal areas. Our empirical results provide a scientific basis for the Chinese government to achieve its non-fossil energy targets through the REC guarantee mechanism. We also provide policy makers with ideas for determining the total amount of REC and adjusting the province's consumption responsibility.